Analysis of Newspaper Coverage of Human Rights Violations in North East Nigeria - Livinus Jesse Ayih; Ezekiel S. Asemah; Ekhareafo O. Daniel (Darul Yasin Al Sys, 2026)
This study examined how two leading Nigerian newspapers, Daily Trust and The Punch, reported human rights violations in North East Nigeria between 2010 and 2020, drawing on agenda-setting and framing theories to assess the depth and orientation of coverage. Using a quantitative content analysis of 374 sampled editions containing 279 human-rights-related items, the study applied descriptive statistics to evaluate prominence, formats, frames, and sources, with substantial inter-coder reliability for content coding (κ = 0.78). The findings reveal high salience, as 73.5% of sampled editions carried human rights content, with coverage predominantly presented in news and feature formats and limited reliance on visual or reader-driven genres. Human interest and responsibility frames dominated, followed by conflict and economic consequences frames, while moral framing appeared least frequently. Security agencies emerged as the most cited sources, surpassing victims/eyewitnesses, government officials, NGOs, and international organisations, indicating strong dependence on official narratives. A chi-square test (χ² = 1.17, p > .05) showed no statistically significant difference in the framing patterns of the two newspapers. The study concludes that, despite sustained attention to human rights violations, reportage often lacks the depth, diversity, and critical scrutiny required to advance accountability. It recommends investment in investigative and long-form reporting, broader framing and sourcing practices, routine follow-ups, enhanced audience engagement, and institutional provision of legal, security, and psychosocial protections to strengthen editorial independence.